Privacy-Preserving Machine Learning: Technological, Social, and Policy Perspectives - Ramadhani, Indri Anugrah; Gunawan, Budi (Indonesian Scientific Publication, 2025)
As machine learning and data mining applications increasingly permeate sensitive domains, concerns over data privacy have intensified. This narrative review aims to synthesize current knowledge on privacy-preserving techniques in artificial intelligence, exploring the technological, socio-cultural, and economic-policy dimensions that shape their implementation. The review employed literature from databases including Scopus, IEEE Xplore, and PubMed, using keywords such as